Pengaruh Pemberian Pupuk Organik Green Giant dan Pupuk Daun Super Bionik Terhadap Pertumbuhan dan Produksi Tanaman Pare - Windy Ade Setiawan; Yudi Triyanto; Khairul Rizal (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
Bitter melon is one of the types of potentially commercial vegetables if cultivated intensively on an agribusiness scale. In addition, bitter melon is a profitable agricultural commodity and trade material in local markets and supermarkets because it contains high nutrition that is complete and all parts of the medicinal plant bitter melon. Green giant is an organic fertilizer, in the form of pellets containing nutrients complete with high cation exchange capacity that will increase the availability of nutrients for plants, safe for the environment. Green Giant can improve physical, chemical and biological soil properties. Improving soil texture and structure is accompanied by neutralizing soil acidity, improving soil aeration and drainage, supporting the development of beneficial microorganisms in the soil and increasing the amount of nutrients that can be absorbed by plants. the application of leaf fertilizer which contains micro nutrients, the deficiencies can be overcome. The soil will avoid fatigue or damage by using leaf fertilizer.Key words : Green Giant, micro nutrients, fertilizer